"Relaxing" incisions in abdominal parietal surgery.: Procedures • results. - Croci, Fabio; Pérez Penco, Ernesto (Cirugía del Uruguay, 1985)
There exist numerous abdominal parietal repairing methods based on !he use of relaxing incisions or as- Presen ado a la Sociedad de Cirugía del Uruguay el 3 de octubre de 14. Prof. Adjun o y Asis·enie de Clínica Quirúrgica. Dirección: Yaguarón 1581 apto. 302, Montevideo (Dr. F. Croci). Procedimientos - resultados Ores. Fabio Croci y Enesto Pérez Penco Clfnica Quirúrgica "A" (Director Prof. Dr. A. Aguiar). Hospital de Clfnicas. Fac. de Medicina. Montevideo. sociatíng relaxing incisions as the basic element in its control. The only methods that are commonly employed and of relative use are !hose applicable to defects of moderate importance, there existing a ful! range of procedures, from very simple to very complex. Methods employed for lateral delects are not systemati• zed and are chiefly used for their sliding capacily. Furthermore, there is no true prospective evidence of results and, therefore, of actual utility. This work is in• tended for rationalization of the use o! said incisions and the retrospective analysis of results obtained.